Fundamentals of materials science and engineering - Callister, William D., Jr., 1940-; Rethwisch, David G. ([Singapore]: John Wiley & Sons, 2022)
"In this sixth edition we have retained the objectives and approaches for teaching materials science and engineering that were presented in previous editions. These objectives are as follows: Present the basic fundamentals on a level appropriate for university/college students who have completed their freshmen calculus, chemistry, and physics courses. Present the subject matter in a logical order, from the simple to the more complex. Each chapter builds on the content of previous ones. If a topic or concept is worth treating, then it is worth treating in sufficient detail and to the extent that students have the opportunity to fully understand it without having to consult other sources; in addition, in most cases, some practical relevance is provided. Inclusion of features in the book that expedite the learning process, to include the following: photographs/illustrations (some in full color); learning objectives; "Why Study . . ." and "Materials of Importance" items (to provide relevance); "Concept Check" questions (to test conceptual understanding); end-of-chapter questions and problems (to develop understanding of concepts and problem-solving skills); end-of-book Answers to Selected Problems (to check accuracy of work); end-of chapter summary tables containing key equations and equation symbols, and a glossary (for easy reference). Employment of new instructional technologies to enhance the teaching and learning processes."--
Includes index.
Catalography
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Materials